«Inoffensive» lexis of conflict (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The author analyses the markers of the conflict which are stylistically and emotionally neutral lexemes, also proving that the language elements, in certain circumstances, can interfere with the process of communication and form the basis of verbal interpersonal conflict. «Inoffensive» vocabulary of the conflict was described and distributed into three thematic groups, depending on the nature of the assessment opponent and measures of disagreement.
Keywords: act of communication; verbal conflict; the lexical marker of conflict; and negative-estimated value